Trade, technology and relative wages: a computable general equilibrium analysis - Winchester, Niven (2002)
The cause(s) of increased wage inequality in developed nations in recent decades is a contentious issue in international economics. In the UK, the ratio of non-manual to manual wages increased by 24.4 percent between 1979 and 1999. Over the same interval, there has been an increase in the relative supply of skilled workers. This suggests that the increase in the relative wage of skilled labour has been driven by a large increase in relative demand for this type of labour. Two candidates commonly cited as the catalyst behind the demand shift are increased trade between developed countries and unskilled-labour-abundant developing nations, and technical change favouring skilled labour.